The Dynamics of Affective Assessment in MI Schools: Challenges and Solutions - Diana Monita; Moh. Ferdi Hasan (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
In this modern education era, affective assessment has become extremely important. This is because affective assessment not only focuses on students' knowledge and skills, but also on their emotional aspects and attitudes. The reality in the field shows that there are still challenges and obstacles in the implementation of affective assessment. Therefore, this research needs to be conducted. The purpose of this research is to understand the dynamics of affective assessment in MI Schools and to seek solutions for challenges in its implementation. The research method used is qualitative research with a Classroom Action Research (CAR) approach, which involves observation, interviews, and document analysis. The results of the research show that affective assessment is generally carried out through observation and recording of student behavior by teachers, as well as input from parents. However, there are still challenges in the implementation of affective assessment, especially related to objectivity and interpretation of results. Several strategies and solutions have been used and proposed, such as training and workshops on affective assessment, the use of more systematic and efficient assessment tools, and collaboration with students' parents. From this research, it can be concluded that improving the quality of affective assessment in MI Schools requires efforts from various parties, not only teachers but also parents and the school community. For further research, it is suggested to conduct experimental research to test the effectiveness of the solutions proposed in this research and the development of more systematic and efficient affective assessment tools.